2015
DOI: 10.1103/physreve.91.022203
|View full text |Cite
|
Sign up to set email alerts
|

Bonded-cell model for particle fracture

Abstract: Particle degradation and fracture play an important role in natural granular flows and in many applications of granular materials. We analyze the fracture properties of two-dimensional disklike particles modeled as aggregates of rigid cells bonded along their sides by a cohesive Mohr-Coulomb law and simulated by the contact dynamics method. We show that the compressive strength scales with tensile strength between cells but depends also on the friction coefficient and a parameter describing cell shape distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 88 publications
3
65
0
1
Order By: Relevance
“…It was shown that the shear strength remains constant due to a compensation between the contact and branch length anisotropies, while force anisotropy and friction mobilization remain constant. As shown previously [6,12], these results confirm that, as the size span of the PSD increases, the system is more and more connected and larger forces tend to be captured by larger particles.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…It was shown that the shear strength remains constant due to a compensation between the contact and branch length anisotropies, while force anisotropy and friction mobilization remain constant. As shown previously [6,12], these results confirm that, as the size span of the PSD increases, the system is more and more connected and larger forces tend to be captured by larger particles.…”
Section: Discussionsupporting
confidence: 75%
“…This has already been observed, also by means of discrete element simulations, for samples with uniform distributions by volume fraction [6,12]. In these cases, only the PSD size span was varied in samples with uniform distributions by volume fraction.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Using high performance GPU's, [73] investigated the size effects in granular mixture flows, whereas [74] used it to simulate fractures in heterogeneous media. Additionally, to bridge the gap between ideal and realistic mixtures, studies have also considered to simulate non-spherical particles using the GPU-based framework, see [75] for triangular particles, [76,77] for convex polyhedrals.…”
Section: Segregation Modelsmentioning
confidence: 99%